Speech Development Factors in Surdopedagogy - Makhmudova Oygul Tokhirjonovna; Yigitaliyeva Muslimaxon Ismoiljon qizi (Scientific Trends, 2025)
Speech development in children with hearing impairments is one of the most complex yet crucial areas of special pedagogy. Surdopedagogy – the science of educating and developing children with hearing loss – emphasizes the systematic integration of linguistic, cognitive, social, and technological factors that promote communication competence. This paper analyzes the main internal and external factors that influence speech development among deaf and hard-of-hearing learners, focusing on psychological, linguistic, environmental, methodological, and technological determinants. It also discusses the pedagogical implications for modern surdopedagogical practice in inclusive and specialized settings.
Keywords: Surdopedagogy, speech development, hearing impairment, communication, linguistic competence, pedagogy, speech therapy, inclusive education.